Notes in colombian herpetology, ii (1944)
The Lizard Genus Echinosaura (Teiidae) in Colombia / Notes on the habits of the Tadpole-Carrying Frog Hyloxalus granuliventris / A New Marsupian Frog (Gastrotheca) from Colombia.